Mindfulness and Sustainable Consumption: A Bibliometric and Systematic Literature Review of Empirical Findings - Gomez-Olmedo, Ana M.; Aranega, Alba Y.; Berenguer, Klaus Ulrich (Transformations In Business & Economics, 2024)
The aim of this paper is based on a systematic bibliometric review of the literature providing an updated analysis of the empirical research on the relationship between mindfulness and sustainable consumption. The structure of the paper comprises a first introductory section, followed by a comprehensive and thorough literature review. The third section discusses the methodology applied following SPAR-4-SLR. The results of a total of 65 studies are then analysed and obtained to help promote various streams of research related to marketing and offer a proven theoretical basis in the business world and implement it in people management. This is followed by a discussion of the findings, and concludes with theoretical and practical implications, along with a discussion of limitations and future research directions. In summary, a further exploration of individual dispositions that may facilitate SCBs and the role of mindfulness seems worth pursuing.